RELEVANCE IMPROVEMENT METHODS OF TEACHING EDUCATIONAL PROGRAMS THROUGH VIRTUAL TECHNOLOGIES - Shyndaliyev , Н.Т.; Shynatay , Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Informatization of the system of science and education is becoming relevant today. Virtual technologies expand the scope of computer technologies in General and make a great contribution to the development of science and education.This field is studied by Kazakh and many foreign scientists. The article reflects the relevance of improving the teaching methods of the educational program through virtual technologies in the training of computer science teachers. The relationship between modern systems and virtual technologies used in education is determined. Methods of teaching the educational program,forms of their representation and virtual technologies used in the virtualization of the educational environment, as well as tools necessary for the organization of teaching methods of the educational program are proposed. The advantages of teaching educational programs in a virtual educational environment using virtual technologies and the new role of the teacher in a virtual educational environment are described. The advantages of training in educational programs in a virtual educational environment through virtual technologies are presented.